2020
DOI: 10.1002/aenm.202001201
|View full text |Cite
|
Sign up to set email alerts
|

The Layered Oxides in Lithium and Sodium‐Ion Batteries: A Solid‐State Chemistry Approach

Abstract: This paper gives an overview of the research carried out on lithium and sodium layered materials as positive electrodes of lithium (sodium)‐ion batteries. It focuses on the solid‐state chemistry contribution to discover new materials and to optimize the properties versus the requirements imposed by the applications. Among, all material structures, which are considered, the layered ones (lithium based), are the best candidates for high energy density batteries for mobile applications. Recently, the homologous N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 201 publications
(223 reference statements)
0
89
0
Order By: Relevance
“…The most frequent ones are P2 and O3, where the numbers indicate the number of TMO layers per unit cell. [9] Structural properties of layered oxides for LIBs and SIBs have been recently discussed by Delmas et al [10] In view of its elemental abundance, price, and environmental friendliness, Mn-rich layered oxides are highly desirable for SIBs. [11][12][13][14] Na x MnO 2 (0.44 < x < 1.0) has been intensively studied since the 1970s with varying parameters of calcination temperature, Na content, and cut-off potential.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent ones are P2 and O3, where the numbers indicate the number of TMO layers per unit cell. [9] Structural properties of layered oxides for LIBs and SIBs have been recently discussed by Delmas et al [10] In view of its elemental abundance, price, and environmental friendliness, Mn-rich layered oxides are highly desirable for SIBs. [11][12][13][14] Na x MnO 2 (0.44 < x < 1.0) has been intensively studied since the 1970s with varying parameters of calcination temperature, Na content, and cut-off potential.…”
Section: Introductionmentioning
confidence: 99%
“…Dating back to 1980, LiCoO was the first chemistry to be successfully implemented in a cathode for LIBs [ 25 , 50 ], and it is still the most widely used chemistry in portable devices. Good ionic and electronic conductivities are key advantages of Co-based cathode; another important feature is the structural stability, which is related with the Co ions redox energy, significantly lower than for Li/Li and graphite, leading to good cation ordering and high theoretical capacity (∼274 mAh·g [ 51 ]), with an operating voltage in the range of 3.8–4.3 V. However, since their electronic band is overlapped with the O : 2p band [ 25 ] (see Figure 6 ) instability related with oxygen release limits the practical capacity to ∼150 mAh·g , as can be shown in Table 1 .…”
Section: The Positive Electrode (Cathode)mentioning
confidence: 99%
“…5,6 Thus, the energy density of the practical SIBs depends on the performance of positive electrodes. Of the various prospective candidates such as layered transition metal oxides 7,8 and polyanionic frameworks 9 , vanadium containing phosphates and fluorophosphates such as Na 3 V 2 (PO 4 ) 3 , 10 NaVOPO 4 , [11][12][13][14] NaVPO 4 F 15,16 and Na 3 V 2 (PO 4 ) 2 F 3 17,18 have attracted huge attention due to satisfactory capacity, high redox potentials and ultra-long cycle life. To understand the structural differences in the frameworks, various polymorphs of NaVOPO 4 have been studied and compared by Aparicio et al They reported that layered α I -NaVOPO 4 with tunnels in the layer exhibits high ionic conductivity due to their high mobility of Na + ions and 3D Na diffusion pathways with low activation energy which facilitates better Na-storage properties.…”
Section: Introductionmentioning
confidence: 99%